Comparative ferrokinetic study with initial and extended iron clearance models. Issue 5 (May 1991) - Howarth, J E; Waters, H M; Hyde, K; Shanks, D; Geary, C G
Abstract : Erythrokinetic studies were performed on 10 patients with chronic myelofibrosis and 11 patients with myelodysplasia (MDS). Values for plasma iron turnover, marrow iron turnover, and erythron transferrin uptake were derived using two ferrokinetic models. One entailed analysis of the extended plasma iron clearance over a number of days, the other comprised analysis of the initial plasma iron clearance during the first few hours of the study. A close correlation was found between the variables quantifying total erythropoiesis (marrow iron turnover and erythron transferrin uptake) in the two methodologies. Functional classifications produced by both models and based on the values for plasma iron turnover, marrow iron turnover, and erythron transferrin uptake were compared. Both models identified functional heterogeneity in the group with myelofibrosis and functional homogeneity within the MDS group. Each method produced comparable data on erythropoiesis. The main reason for analysing the extended plasma iron clearance is to differentiate levels of effective and ineffective erythropoiesis. The short analysis presents the practical advantages associated with a one-day study. This could be further enhanced if the level of effective erythropoiesis could be clearly defined.